Utilization of Digital Technology in Educational Administration and Communication in Islamic Elementary Schools - Ricky Febrian; Dwi Jayanti; Dea Anisa; Rohayati; Ria Juliana (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the optimization of digital technology utilization in educational administration and communication at Madrasah Ibtidaiyah Nurul Istiqomah Al-Musri, West Lampung. This research employs a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings show that digital technology has been utilized in student data management, financial administration, learning administration, communication with parents, and document archiving; however, its implementation remains partial and not yet integrated, indicating a transitional phase toward digital-based systems. Supporting factors include leadership, availability of devices, and awareness of technology importance, while inhibiting factors involve limited human resource competencies, inadequate infrastructure, resistance to change, and lack of training. Optimization efforts have been carried out through motivation, self-learning, and gradual provision of facilities, but they remain unstructured and require strengthening through integrated systems, continuous training, and improved infrastructure. This study contributes to the development of digital-based Islamic education management at the elementary level.